2021
DOI: 10.3390/en14227561
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Growth Behavior Analysis of Slagging Rings in Rotary Kiln-Type Hazardous Waste Incineration Systems

Abstract: Rotary kiln incineration technology has the advantages of strong material adaptability and a simple treatment process and has been widely used in hazardous waste treatment. However, the actual incineration process has caused problems such as ring formation in the treatment system due to the lack of research on the slagging mechanisms. In this paper, slagging phenomena occurring in the second half of the rotary kiln, the exit flue of the secondary combustion chamber, and the wall of the quench tower are analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Some scholars have shown that deposits in the rotary kiln are characterized by large amounts of Na, Si, Cl, Ca, and Fe. Its molten phase is mainly formed by alkali metal salts with low melting points, such as sodium chloride (801 • C) [12,35]. Zhu et al [36] found that the main chemical compositions of the hazardous waste incineration residue were SiO 2 , Al 2 O 3 , Fe 2 O 3 , CaO, and MgO.…”
Section: Crystal Phase Composition Of Depositsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars have shown that deposits in the rotary kiln are characterized by large amounts of Na, Si, Cl, Ca, and Fe. Its molten phase is mainly formed by alkali metal salts with low melting points, such as sodium chloride (801 • C) [12,35]. Zhu et al [36] found that the main chemical compositions of the hazardous waste incineration residue were SiO 2 , Al 2 O 3 , Fe 2 O 3 , CaO, and MgO.…”
Section: Crystal Phase Composition Of Depositsmentioning
confidence: 99%
“…Then, it is discharged from the end of the kiln into the cooling system [11]. This process has the advantages of low capital investment, strong adaptability, large production capacity, and flexible operation [12][13][14]. The iron oxides in the dust are reduced to metallic iron or low-valence iron oxide; at the same time, the zinc oxides are reduced to metallic zinc under high-temperature conditions in the rotary kiln using carbon as the fuel.…”
Section: Introductionmentioning
confidence: 99%